Analytical Methods for Determination of Ketoprofen Drug: A review - Jasim Shamar; Sumayha Abbas; Zahra Abbas (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2022)
Ketoprofen has recently been proven to offer therapeutic potential in preventing cancers such as colorectal and lung tumors, as well as in treating neurological illnesses. The goal of this review is to show the methods that have been used for determining ketoprofen in pharmaceutical formulations. Precision product quality control is crucial to confirm the composition of the drugs in pharmaceutical use. Several analytical techniques, including chromatographic and spectroscopic methods, have been used for determining ketoprofen in different sample forms such as a tablet, capsule, ampoule, gel, and human plasma. The limit of detection of ketoprofen was 0.1 ng/ ml using liquid chromatography with tandem mass spectrometry, while it was 0.01- 0.30 µg/ ml using high performance liquid chromatography and 0.00004 - 0.436 µg/ ml, 0.82 µg/ ml, 1.0  µg/ ml, 10  µg/ ml and 208.5 - 237.6  µg/ ml  using flow injection, electrokinetic chromatography, capillary electrophoresis, gas chromatography-flame ionisation detection and derivative infrared spectroscopy respectively.